Miliary Tuberculosis: A Case Report Highlighting the Diagnostic Challenges Associated With the Condition - Ilyas, Usman; Mahmood, Abrahim; Pansuriya, Amee M; Umar, Zaryab; Landry, Ian (Curēus (Palo Alto, CA), 2022)
End-stage renal disease requiring chronic dialysis is an immunocompromised state which increases the risk of tuberculosis development and its spread. Due to the high frequency of non-specific or "decoy" symptoms at presentation and frequent extrapulmonary involvement, diagnosis of tuberculosis is a significant challenge. Therefore, it is correctly labeled as 'Tuberculosis; the great imitator' as it can mimic various other disease processes, causing confusion and testing of subsystems involved in the disease process, which come back as abnormal, leading to a vicious cycle. Missing the diagnosis leads to grave consequences, especially in a patient with a miliary form of tuberculosis, as the prognosis with any delay in treatment is poor. High diagnostic suspicion is required to promptly diagnose and treat the condition, especially in a resource-rich setting where tuberculosis is uncommon. Here, we report a patient with miliary tuberculosis who presented with a chief complaint of chronic diarrhea and fecal continence, with prior recent negative interferon-gamma release assay testing. Due to every organ system involved, multiple subspecialties were on board, with a broad differential in mind, including malabsorption syndromes, neoplasia, infections, amyloidosis, and autoimmune disorders, and therefore, numerous tests were performed. However, despite all efforts, the diagnosis was delayed significantly, leading to the unfortunate demise of the patient. The case report sheds light on unique clinical features of miliary tuberculosis, diagnostic findings, and a reminder to always keep tuberculosis high in the differential in an appropriate clinical setting.